Motherhood Experiences of Visually Impaired Women – A Feminist Disability Studies Approach - Nikolett Rékasi; Gabriella Papp (Fogyatékosság és Társadalom)
It is important to separate disability studies research by gender because women may have different experiences from men. Research on specific situations faced by women, such as motherhood, is particularly important in order to get a broader picture of the oppression of disabled people. In our study, we explored the motherhood experiences of five visually impaired Hungarian women using a feminist disability studies approach. We conducted narrative life history interviews with them. We combined two qualitative research methods, Grounded Theory and narrative life history interviews, to explore aspects of the topic that are hardly accessible and to create a frame of the experiences. We used MAXQDA 2022. Our research focuses on the question: What characterises visually impaired mothers’ experience and lived experiences of motherhood? According to our research, fear of passing disability on to their children plays a role in their decision-making process, although there is no ground for exclusion. Visually impaired women also experience obstetric violence. Regarding infant care and parenting, they turn to alternative techniques which they either invent themselves, learn at the particular rehabilitation module Special Techniques of Infant Care for visually impaired Persons or from other visually impaired parents. In conclusion, mothers might need alternate solutions, but this is possible.